A legal study on the usage and disposal of plastic shopping bags in Malaysian supermarkets / Mohd Firdaush Jaafar, Amir Nur Ikhwan Amernudin - Jaafar, Mohd Firdaush; Amernudin, Amir Nur Ikhwan (2008)
The title of this research is "A Legal Study on the Usage and Disposal of Plastic Shopping Bags in Malaysian Supermarkets". This research is done to address the environmental problems in Malaysia. Recently, Malaysia had suffered from environmental problems such as air pollution and water pollution. The main reason for these problems is the uncontrolled usage of plastic shopping bags and the problem with the disposal system. We need to find the best solution to overcome these problems in order to avoid a greater damage to the environment. Since we don't have a specific regulation regarding the usage and disposal of plastic shopping bags, we need to look at other countries and how they had adopted the regulations regarding this matter. From this, we can find the best solution and the most suitable way to be implemented in Malaysia. We also need to take into account few aspects such as the implementation and the enforcement in order to suits our society. In the end of this research, we will come out with few suggestions for the government to take action in order to overcome this problem. We hope that with the suggestions, we can help the environment for future generation